Estrategias de resistencia cotidianas: Profesionistas Indígenas ante el racismo anti-Indígena en México - Bautista Pérez, Judith (El Colegio de México, 2022)
Despite to an increasing public and academic attention to racism in Mexico, we still need to build a consistent understanding that racism is a system that has historically organized and distributed privileges and power in multiple ways. It continues to be difficult to recognize anti-indigenous racism as a social fact and as an important category for academic analysis. Indigenous people make decisions and design strategies to survive racism in each case or situation. Here I present an analysis of the strategies that professional indigenous people have develop to endure, challenge and contest racism. I have organized these strategies under the categories of: assimilation, double effort, negation and confrontation. All this from a critical stance in front the social tendency to limit racism to individual experiences because from that this position results in an isolated and emptied interpretation of social and historical content. In addition, through testimonies of indigenous men and women I present an argument against underestimating the consequences of racism in the lives of racialized subjects.